Systematic review for the development of a core outcome set for monofocal intraocular lenses for cataract surgery - Tarricone, Rosanna; Rognoni, Carla; Ciarlo, Anita; Giabbani, Ilaria; Novello, Leonardo; Balestrieri, Marco; Costa, Giacomo; Favuzza, Eleonora; Mencucci, Rita; Taroni, Leonardo; Tognetto, Daniele; Giglio, Rosa (Frontiers in Medicine, 2024)
Introduction The aim of the study was to define a core outcome set (COS) to be measured following cataract surgery for the postoperative evaluation of monofocal intraocular lenses (IOLs). Compared to current COSs, the present work provides updates considering the advances in the technology due to the development of new generation monofocal IOLs, which are characterized by a safety profile comparable to standard monofocal IOLs but with an extended range of intermediate vision. Methods Healthcare professionals (ophthalmologist surgeons) and patients were involved in the selection of outcomes to be included in the COS, starting from a list of indicators retrieved from a systematic literature search. The search considered observational studies with both a retrospective or prospective design, case studies and classic randomized controlled trials (RCTs). A mixed methodology integrating a Delphi-driven and an expert panel approach was adopted to reach an agreement among clinicians, while patients were involved in the completion of a questionnaire. Results The final COS included 15 outcomes. Eleven outcomes, all clinical, were considered for inclusion after a joint discussion among ophthalmologists; seven outcomes were linked to visual acuity, while the remaining to contrast sensitivity, refractive errors, aberrations and adverse events. Measurement metrics, method of aggregation and measurement time point of these outcomes were specified. The most important aspects for the patients were (1) quality of life after cataract surgery, (2) the capacity to perform activities requiring good near vision (e.g., reading), (3) spectacle independence, and (4) safety of movements without fear of getting hurt or falling (intermediate vision). Discussion In a context with limited healthcare resources, it is important to optimize their use considering also the preferences of end-users, namely patients. The proposed COS, developed involving both ophthalmologists and patients, provides an instrument for the postoperative evaluation of different technologies in the context of monofocal IOLs, which can be used not only in clinical trials but also in clinical practice to increase the body of real-world evidence.